Stability Measurements of the Baha System in Children. (23rd August 2013) - Felton, Mark; Feltham, Penny; Andrew, Rachel; Bruce, Iain
Abstract : Objectives: Bone conduction implant (eg, Baha®) stability can objectively be measured over time using radio‐frequency analysis (RFA). Adult studies suggest that the Cochlear Baha BI300 Implant® may be loaded as soon as the soft tissue wound is healed. We aim to discuss implant stability in children using RFA measurements. Methods: Consecutive children having a Cochlear Baha BI300 Implant had RFA measurements taken peri‐operatively, 1 week post‐surgery, within 3 months of surgery, and then subsequently at least 3 monthly. RFA measurements were measured at loading of the hearing processor and at 1 week post‐loading. Standard practice has been to load the implant at 3‐6 months postoperatively. Results: Nine children had 10 Cochlear Baha BI300 implants® (8 unilateral and 1 bilateral) with a mean age of 9 years 4 months (4 years 9 months to 13 years 5 months). The mean time to loading of the hearing processor was 3.3 months (3 to 5 months, n = 9). Mean follow‐up was 9 months (6 weeks to 23 months). Peri‐ and postoperative RFA measurements will be discussed with 6 children having RFAs sufficiently high for hearing processor loading much earlier post‐implantation. Implant stability was maintained after loading with the hearing processor. Conclusions: This study indicates that a larger study is warranted to evaluate both the role of sequential RFA measurements in the timings of Baha hearing processor loading and the possibility of loading at 4‐6 weeks in selected children. Subsequently RFA measurements may also be used to decide between single‐ and two‐stage surgery.